1987
DOI: 10.1017/s0950268800061999
|View full text |Cite
|
Sign up to set email alerts
|

Restriction enzyme fingerprinting of trimethoprim resistance plasmids

Abstract: SUMMARYRestriction enzyme fingerprinting was applied to 72 transferable trimethoprim resistance plasmids to examine aspects of their epidemiology and molecular relatedness.These plasmids had previously been divided into 25 groups according to differences in mol. wts and in antimicrobial resistance determinants. Restriction enzyme fingerprinting allowed the plasmids to be further divided into 44 different groups. The groups based on molecular weight and resistance patterns often, but not invariably, corresponde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1989
1989
1995
1995

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…The findings from our study confirm those of others (12,13,19) However, other studies have shown that both of these transposons may occur in isolates from the tropics and may contribute to the widespread dissemination of resistant genes between species (8,20). The number of fragments generated by single enzymes is not sufficiently discriminatory to be useful in plasmid classification, but combining the results from two different digests does provide a basis for classification.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The findings from our study confirm those of others (12,13,19) However, other studies have shown that both of these transposons may occur in isolates from the tropics and may contribute to the widespread dissemination of resistant genes between species (8,20). The number of fragments generated by single enzymes is not sufficiently discriminatory to be useful in plasmid classification, but combining the results from two different digests does provide a basis for classification.…”
Section: Discussionsupporting
confidence: 69%
“…As part of a study of antibiotic resistance in enteric flora isolated from children in Khartoum, Sudan, we have investigated the use of restriction endonuclease digestion to characterize resistant transconjugant plasmids. Resistance pattern pKc [1][2][3][4][5][6][7][8] Ap Su Tm Sm pKc9,10 TcC pKcl11 Ap Tm pKc [12][13][14][15] Tm pKc 16 Ap Tc PKc 17 Ap Su Tm Sm C pKc 18,19 ApTcSuTmSm pKc 20 Ap Su Tm pKc 21 Ap Tc Su Tm Sm C pKc 22 Ap Tc C pKc 23,24 Ap PATIENTS AND METHODS…”
Section: Introductionmentioning
confidence: 99%
“…This situation is not restricted to Gm R-plasmids in S. typhimurium. Trimethoprim Rplasmids in E. coli [16] and ampicillin R-plasmids [17] show similar divergence. However, this contrasts the molecular conservation of SSPs of S. typhimurium [9], S. enteritidis and S. dublin and demonstrates that the individual plasmid components of plasmid profiles have the capacity to evolve at different rates.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmid DNA was extracted by the method of Kado and Liu [19]. For endonuclease restriction analysis, plasmid DNA was prepared and purified as described by Kraft and co-workers [20]. Restriction enzymes Hind III, Hind II and Cla I were used as recommended by the manufacturer (Bethesda Research Laboratories Ltd, U.S.A.).…”
Section: Plasmid Profile and Endonuclease Restriction Analyismentioning
confidence: 99%